Investigation of Adolescents' Recreational Sports Awareness - Erdal Zorba; Mutlu Türkmen; Baglan Yermakhanov; Ümit Doğan Üstün (ümit doğan üstün, 2021)
The aim of this study was to examine the sports awareness of adolescents who participate in recreational sports as active or passive in terms of various variables. The study was designed as a quantitative research and 231 high school students from Hatay who were selected with convenience sampling method participated in the research. To collect data the "Sports Awareness Scale" developed by Uyar and Sunay (2020) was used. In the evaluation of the data, SPSS 23 package program for Windows was used and independent samples t test and one-way analysis of variance test were applied at 95% confidence interval. According to the analyzed results, the sports awareness of boys is higher than girls' in the "sports knowledge and discrimination" sub-dimension (p<0.05). Besides, participants doing active sports have higher sports awareness in all sub-dimensions than the passive sports participants (spectators), and participants with a family member doing active sports have higher sports awareness in the "social and individual benefit" sub-dimension than other participants (p<0.05). However, age do not make a significant difference in the variable sports awareness (p> 0.05).